2013
DOI: 10.1002/ldr.2211
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Controls on Fallow Carbon Dioxide Flux in a Single‐Crop Rice Paddy, Japan

Abstract: Soil organic carbon (SOC) is one of the important measures of soil fertility and sustainability in arable lands. With continuous CO 2 flux measurements, this study assessed the SOC decomposition and its environmental controls at both half-hourly and season-long scales in a single-crop rice (Oryza sativa L.) paddy during three fallow periods between 2004 and 2007. Measurements were made on a gray lowland soil sited in eastern Japan using the eddy covariance method. Ecosystem respiration was strongly affected by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 30 publications
0
29
1
Order By: Relevance
“…They obtained a higher CO 2 evolution rate at the field capacity than that at 60 of the field capacity. This finding does not appear to be consistent with the negative correlation between CO 2 flux and soil moisture reported by Ono et al 2015 . In actual fields, soils were stacked and layered, and water continuously moves vertically and horizontally.…”
Section: Introductioncontrasting
confidence: 90%
See 1 more Smart Citation
“…They obtained a higher CO 2 evolution rate at the field capacity than that at 60 of the field capacity. This finding does not appear to be consistent with the negative correlation between CO 2 flux and soil moisture reported by Ono et al 2015 . In actual fields, soils were stacked and layered, and water continuously moves vertically and horizontally.…”
Section: Introductioncontrasting
confidence: 90%
“…At a field scale, Ono et al 2015 measured the CO 2 fluxes during three FSs in a normally cultivated rice paddy in central Japan using the eddy covariance method and showed that approximately 50 of the crop residues left in the field after the harvest were decomposed during FS. The time course of the observed CO 2 flux during FS was positively correlated with soil temperature and negatively correlated with soil moisture under very wet conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Meteorological data and ecological characteristics such as plant height, leaf area, and biomass have been monitored at the site since 1999 Ono et al, 2013 . A rectangular plot of 100 54 m was cultivated with 'Koshihikari' rice Oryza sativa L. using established methods. Further details of the site and experimental crop are given in previous studies Miyata et al, 2005;Saito et al, 2005;Mano et al, 2007;Ono et al, 2008Ono et al, , 2013Ono et al, , 2015 2.2 Plant height measurement method 2.2.1 Plant height measurement system A weatherproof time-lapse camera PlantCam, Wingscapes, Alabaster, AL, USA was used to capture images of rice plants at the site. The camera has a 4.0 megapixel CMOS sensor and the 35-mm-equivalent focal length is 45 mm lens field of view of 52° .…”
Section: Study Site and Experimental Cropmentioning
confidence: 99%
“…A rectangular plot of 100 × 54 m was cultivated with 'Koshihikari' rice (Oryza sativa L.) using established methods, and the transplanting and harvesting date were May 2nd and September 11th, respectively. Further details of the site and experimental crop are given in previous studies Saito et al, 2005;Mano et al, 2007;Ono et al, 2008Ono et al, , 2013Ono et al, , 2015Mano, 2017).…”
Section: Experimental Sitementioning
confidence: 99%